The Fund's Income Position for FY 2021 : Actual Outcome. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2021)
This paper reports on the Fund's income position for FY 2021 following the closing of the Fund's accounts for the financial year and completion of the external audit. Overall FY 2021 net income amounted to SDR 4.8 billion or SDR 0.7 billion higher than estimated in April, mainly reflecting a larger than anticipated gain reported under IAS 19 (the accounting standard for employee benefits) and endowment returns exceeding earlier projections.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Income Outlook; Monetary Policy; Political Economyretirement Plan Obligation; Transparency Policy